A numerical investigation on the yield surface for shallow foundations embedded in sand. (February 2018) - Govoni, Laura
Abstract: This paper presents a numerical study on the drained response of a shallow foundation subjected to planar combined loads. Plane strain conditions are assumed and different initial foundation depths and values of vertical penetration are considered. Data from centrifuge experiments of surface and buried foundations available in literature, are used to assess the ability of the model to reproduce the essential features of the experimentally observed behaviour. Interpreted within the context of existing work-hardening plasticity models applied to the soil-foundation system and presented in terms of load–displacement curves and load paths, the results of the numerical analyses provide new evidence of the effects of the embedment on the yield surface for a shallow foundation.